EXHIBIT B EMPLOYMENT REQUIREMENTS - PHYSICAL STANDA RDS, NO-SMOKING CLAUSE - MIDDENDORF,LC (Tufts Archival Research Center, 2007)
Letter from labor relations representative of San Mateo Fire Fighters to the Deputy City Manager protesting an application clause requiring employees maintain physical standards and to agree to a non-smoking clause. Argues that the inclusion of such clauses is subject to collective bargaining discussions, and that no such discussions have occurred, thus invalidating the application.